2016
DOI: 10.1111/jcal.12126
|View full text |Cite
|
Sign up to set email alerts
|

A MOOC based on blended pedagogy

Abstract: We describe three iterations of a Massive Open Online Course (MOOC) developed from online preparation materials for a reformed introductory physics classroom at the Massachusetts Institute of Technology, in which the teaching staff interact with small groups of students doing problems using an expert problem‐solving pedagogy. The MOOC contains an e‐text, simple checkpoint problems and homework. We show how certain course design aspects affect student behaviour: (a) frequent quizzes correlated with students rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…Evans, Baker, and Dee (2016), for instance, found that the use of specific words in video titles, such as “intro” and “overview”, substantially increased viewership by MOOC participants. Rayyan et al (2016) observed that more frequent quizzes improved the likelihood of learners reading the supporting materials and more difficult homework was correlated with increasing time on task.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evans, Baker, and Dee (2016), for instance, found that the use of specific words in video titles, such as “intro” and “overview”, substantially increased viewership by MOOC participants. Rayyan et al (2016) observed that more frequent quizzes improved the likelihood of learners reading the supporting materials and more difficult homework was correlated with increasing time on task.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Online open courses under MOOC mode enters into the university classroom which is not just a simple recording and tailoring of the professional course but many parallel spiral teaching sectors including curriculum guidance, theory teaching, practice analysis and later expansion of knowledge, is a complete professional network teaching system [15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Rayyan also stressed that, along with the rapid development of modern information technology, various aspects of the country's educational philosophy, educational management, educational system and teaching organization and methods have been changed accordingly, and the "Internet plus" has risen as a national strategy. Followed by the rapid rise of online education, due attention and concerns were also aroused [5].…”
Section: Literature Reviewmentioning
confidence: 99%